IDENTIFIKASI BUDAYA ORGANISASI PADA BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN (BKPP) KABUPATEN SRAGEN DENGAN MENGGUNAKAN ORGANIZATIONAL CULTURAL ASSESSMENT INSTRUMENT (OCAI) - Nur Endah Widyastuti (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2018)
Abstract Achievement of organizational goals or performance is seen no longer only depends on the system of division of labor alone but also on the human aspect, as the organizer of the organization. As a regional apparatus organization undergoing structural changes along with its main duties and functions, BKPP of Sragen regency faces changes in the formulation of its strategic plan so that it becomes the momentum of the introduction of organizational culture and its integration in the strategy of achieving the performance targets set out in the planning. This study aims to identify the current organizational culture in BKPP of Sragen regency and the type of organizational culture that is expected in the future. With respondents of all employees at BKPP of Sragen regency, the identification of organizational culture type was done by using Organizational Cultural Assessment Instrument (OCAI) instrument developed by Kim Cameron and Robert Quinn. From the research result, the result of dominant organizational culture in BKPP of Sragen Regency is Clan type which prioritizes family atmosphere, mutual commitment, participation and human resource development. The expectations of future employees are also unchanged, but the current hierarchy culture diminishes its role as the type of ad hoc culture increases. This identification is expected to be an input for leadership and management in formulating strategies for achieving organizational performance. Keywords: Organizational Culture, performance achievement strategy, OCAI